The Role of Word-of-Mouth and Official Concerns in Student Course Selection - Sever, Serkan (Journal of Policy Options, 2023)
This study aims to investigate the factors influencing students' course selection process, with a particular focus on how these factors can be understood from a marketing perspective. To gather qualitative insights, three focus groups were conducted. The data from these discussions revealed that participants' responses generally fell into two broad categories: evaluations based on word-of-mouth (WOM) and evaluations based on official concerns. The evaluations related to word-of-mouth highlighted several important factors. Students emphasized the significance of instructors’ in-class performance, noting that how well an instructor delivers content and engages with students plays a crucial role in their course selection. Another factor that emerged was the attractiveness of course-related virtual environments. The quality and appeal of online resources associated with the course, such as course websites or discussion forums, were important considerations for students. Additionally, the toughness of course assignments and the fairness of grading policies were key aspects that students considered when choosing courses. They tended to favor courses where they felt the workload and evaluation methods were manageable and transparent. On the other hand, evaluations based on official concerns brought to light the importance students placed on the academic and practical experience of instructors. Students valued instructors who had a strong academic background and relevant practical experience, viewing these attributes as indicators of the quality and relevance of the course. The use of computer-enhanced learning technologies also featured prominently in students' decision-making process. The integration of digital tools and technologies in teaching was seen as a significant factor that could enhance the learning experience. The study suggests that, much like consumers in the marketplace, students engage in a careful decision-making process when selecting courses. They actively seek out reliable information, primarily through word-of-mouth from senior students who share their experiences and opinions about courses and instructors. In this context, the performance of courses and instructors is evaluated in a manner similar to how consumers assess products and services, with word-of-mouth playing a critical role in shaping students' perceptions and choices. This insight highlights the importance of understanding the various factors that influence students' course selection, as these can inform more effective strategies in academic marketing and course design, ensuring that offerings are better aligned with students' needs and preferences.